3-(Nitromethylene)oxetane: a very versatile and promising building block for energetic oxetane based monomers. Issue 8 (11th March 2022) - Born, Max; Fessard, Thomas C.; Göttemann, Lucas; Karaghiosoff, Konstantin; Plank, Jakob; Klapötke, Thomas M.
Abstract : 3-(Nitromethylene)oxetane was identified as a promising scaffold for the straightforward synthesis of energetic oxetane monomers via conjugate addition. The use of tetrazoles provided compounds with exciting properties superior to the prior art. Abstract : In the field of energetic materials, older developments ( e.g., RDX, ONC, CL20) are increasingly replaced by more environmentally benign, less expensive and likewise or more powerful compounds. This is mainly achieved through nitrogen-rich motifs like tetrazoles. However, such materials are mostly used as formulations containing polymeric energetic binders. Unfortunately, prior art binders show very poor performances and therefore reduce the overall performance. To address this problem, new monomers with enhanced performance are a prerequisite. Since the majority of energetic binders is oxetane-based, we chose 3-(nitromethylene)oxetane as a promising building block. It exhibits an explosophoric group, has recently become commercially available and provides suitable monomers by elegant and cost-efficient one-pot syntheses via conjugate addition. Herein, we report derivatives based on 1 H -tetrazole, 1 H -tetrazole-5-amine and the rather exotic but extremely powerful primary explosives 5-azido-1 H -tetrazole (5AzT) and 5-nitro-2 H -tetrazole (5NT). The sensitivities toward external stimuli like impact, friction, and electrostatic discharge were assessed by BAM standard procedures. As all molecular structures were elucidated by X-ray diffraction, Hirshfeld analysis was applied to explain the surprisingly low sensitivities found for the 5AzT- and 5NT-derivatives. Further, the compounds were studied by vibrational- and multinuclear NMR spectroscopy ( 1 H, 13 C, 14 N), differential scanning calorimetry, and elemental analysis. Their performance was calculated using the EXPLO5 V6.04 thermochemical code. Based on obtained values, the 5AzT- and 5NT-derivatives outperform prior art energetic oxetanes and TNT. Therefore, their performance was additionally demonstrated and evaluated by a small-scale shock reactivity test (SSRT).